Simulation of the stress-strain state of concrete columnswith pre-compress high-strength reinforcement - Kholod, P. F.; Shmyh, R. A. (Видавництво Львівської політехніки, 2014)
This article discusses the method of determining the stress-strain state of concrete columns with pre-compress high-strength reinforcement based on discrete representation of designs using real charts of the s-e concrete and reinforcement using a computer. This technique allowed us to simulate the work of columns at all stages of loading up to the destruction. Herewith at each stage of loading we get the deformation and stress in the concrete and reinforcement throughout the all height of the section. This technique allows us to take into account prestressing in the reinforcement which takes place at the stage of manufacturing. In addition, it provides an opportunity to simulate the destruction of columns and determine their bearing capacity. Calculations of the experimental models of columns, that were made using this technique shown in most cases good coincidence of results.Розглянуто методику визначення напружено-деформованого стану залізо- бетонних колон з попередньо стиснутою високоміцною арматурою на базі диск- ретного представлення конструкцій з використанням реальних діаграм s-e бетону та арматури за допомогою ЕОМ. Запропонована методика дала змогу промо- делювати роботу колон на всіх стадіях завантаження включно з руйнуванням. На кожній стадії завантаження виникають деформації та напруження в бетоні та арматурі по всій висоті перерізу. Методика також дає змогу врахувати попередні напруження в арматурі, які існують на стадії виготовлення. Крім цього, вона дає можливість промоделювати руйнування колон та визначити їх несучу здатність. Виконані за допомогою запропонованої методики розрахунки експериментальних зразків колон показали переважно достатньо добрий збіг результатів.
Keywords: concrete column; the stress-strain state; the hypothesis of plane sections.; залізобетонна колона; напружено-деформований стан; гіпотеза плоских перерізів